Research on Value and Influence of Chinese Traditional Culture in Contemporary Cultural and Creative Arts Industry - Chen, Tingkun (International Journal of Social Sciences and Public Administration, 2024)
This paper deeply discusses the value and influence of Chinese traditional culture in the contemporary cultural and creative arts industry. First of all, it introduces the basic concept, development course and the role of Chinese traditional culture and cultural and creative arts industry in today’s social and economic development. Secondly, it analyzes the application practice of traditional Chinese cultural elements in the cultural and creative arts industry, including product design, creative planning and value dissemination. Then, it deeply analyzes the positive impact of calligraphy, painting, ceramics and other representative fields on the contemporary market after combining modern design concepts. At the same time, the possible problems and challenges in the process of integration are discussed. Finally, this paper summarizes the role of the government in promoting cultural exchanges between China and foreign countries, and looks forward to the future development.